Inheritance INHERITANCE OF YIELD-RELATED MORPHOLOGICAL CHARACTERISTICS IN F1 TOBACCO HYBRIDS : There is no subtitle - Korubin - Aleksoska, Ana (Journal of Agricultural Sciences (Belgrade), 2023)
Abstract: The aim of this work was to study the mode of inheritance of the number of leaves per stalk and the length, width and area of the leaves from the middle belt of the stalk – traits directly related to the yield, in the offspring of the first generation. Investigations were made with four parent tobacco varieties of different types in the role of mother (three of the type Prilep: P-23, П 18-50/4, П 76/86 and one of the basmak type - МС 8/1) and Burley B-1-91 in the role of father, and their four F1 hybrids. The crossings were made in 2018, 2019 and 2020, and the experiment with the parent genotypes and their hybrids was set up in 2019, 2020 and 2021, on field trial in Scientific Tobacco Institute – Prilep in a randomized block design with four replications. All appropriate cultural practices were applied during the growing season. The research data shown in the paper indicate the fact that in the hybrids there is no occurrence of heterosis for the studied traits. The found mode of inheritance is an indicator of good successive selection of individuals in future generations and quick fixation and stabilization of the traits. The hybrids: P-23 x B-1/91, P 18-50/4 х B-1/91, P-76/86 х B-1/91 and MS 8/1 х B-1/91, represents a very interesting material for future tobacco breeding activities.
Keywords: tobacco, hybrids, morphological traits, inheritance, intermediate, dominance, heterosis.